Long-term Cost-effectiveness of Insulin Degludec Versus Insulin Glargine U100 in the UK: Evidence from the Basal-bolus Subgroup of the DEVOTE Trial (DEVOTE 16) - Pollock, Richard F. (Appl Health Econ Health Policy, 2019)
OBJECTIVES: To evaluate the cost-effectiveness of insulin degludec (degludec) versus insulin glargine 100 units/mL (glargine U100) in basal–bolus regimens for patients with type 2 diabetes (T2D) at high cardiovascular (CV) risk based on the DEVOTE CV outcomes trial. METHODS: A microsimulation model, informed by clinical outcomes from the subgroup of patients using basal–bolus insulin therapy in DEVOTE (NCT01959529) and by the UKPDS Outcomes Model 2 risk equations, was used to model direct costs (2018 GBP) and effectiveness outcomes [quality-adjusted life years (QALYs)] with degludec versus glargine U100 over a 40-year time horizon. The model captured the development of eight diabetes-related complications, death, severe hypoglycemia and insulin dosing. This analysis was conducted from the perspective of National Health Service (NHS) England. RESULTS: Treatment with degludec versus glargine U100 in basal–bolus regimens was associated with improved clinical outcomes at a higher cost per patient [incremental cost effectiveness ratio (ICER): £14,956 GBP/QALY]. Degludec remained cost effective versus glargine U100 in all exploratory sensitivity analyses, with ICERs below the widely accepted willingness-to-pay threshold, although the result was most sensitive to assumptions regarding the persistence of treatment effects. CONCLUSIONS: Our long-term modeling analysis suggested that degludec was cost effective (from the perspective of NHS England) versus glargine U100 in basal–bolus regimens for patients with T2D at high CV risk. Our findings raise important questions regarding how to model the health economics of diabetes therapies. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40258-019-00494-3) contains supplementary material, which is available to authorized users.